From novice to expert: assessment of the levels of expertise of South African Chartered Accountants and Auditors in an academic and professional programme using the Dreyfus's Five-Stage Model of Skills Acquisition - West, Sumaya (School of Education, 2017)
Knowledge in professional and business related courses are grounded in real-world business contexts, which influence the theoretical aspects of an academic programme. Most students in South Africa lack prior business and auditing knowledge, which makes it difficult for them to transfer the theoretical business knowledge, skills and attributes acquired in an educational setting, to the workplace setting. The challenge for auditing educators is to facilitate the acquisition and transfer of theoretical auditing knowledge in preparation of and application for the workplace. Research studies suggest that there is a key dilemma within continuing professional education and development, which mainly relates to the tension between the academic knowledge, skills and attributes and the knowledge, skills and attributes required in professional auditing practice. The purpose of this qualitative study was to assess and compare the development of professional competencies and related expertise of different individuals at different stages in their professional auditing careers. The Dreyfus's five-stage model of skill acquisition (Dreyfus's model) offers a useful theoretical framework for understanding how individuals acquire knowledge and skills through formal instruction and experience. The five stages of the Dreyfus model are identified as novice, advanced beginner, competent, proficient and expert. In this study, the adapted Dreyfus's model was used to assess the knowledge and skills needed of auditors at various stages in an academic and professional training programme in South Africa. Using ten semi-structured interviews, this study highlights the differences in the levels of expertise between experienced auditors and auditors at the novice stage of proficiency. Participants in this study included audit graduates, audit trainees and audit managers. The study found that there were distinct stages in skills development, generally in line with those suggested by the Dreyfus's model, and that there were major shifts in individuals' practice with the development of professional expertise. Central to the movement from one stage to the next is the way in which meaningful connections are made between what is already known (theory) and its application (practice). In developing a framework for understanding what auditing knowledge, skills and experiences are required at various stages, this study informs further development plans for educational workplace settings that are specifically designed for individuals to progress from one developmental stage to another.